Analysis of SocialCultural Factors Influence to the Children in Conflict with Law: A Case Study in 3 Regencies and Municipality of Bengkulu Province, Indonesia - Sri Putri Permata; Muria Herlina (Asian Social Work Journal, 2019)
This research aimed to analyze sociocultural factors among children in conflict with law in the villages of 3 regencies and 1 municipality in Bengkulu Province. Data were collected through observation, in depth interview as well as documentation study. 15 peoples was selected as informants which consist of 6 formal and informal leaders, 6 children in conflict with law, 2 parents, and a social worker. This research finding showed that in the villages most villagers were farmers who spent almost all day for work. This impacted in decreasing time to interact with their children and surrounding neighbors. On the other side, social control were growing weaken. It was indicated by degradation of sociocultural as well as religious values in community. Social status was valued from one’s belonging. Normative customary sanctions were not implemented strictly anymore. Both formal and informal leaders practiced bad behavior. Impact of technology such as uncontrolled use of smart phone had negative impact to the juvenile. This research concluded that there were some changes in sociocultural values which interacted in case of children in conflict with law. From this finding, the efforts to strengthen family functions were needed besides optimizing the roles of law, customary and religious institution as well.